THE DEVELOPMENT OF PROFESSIONAL COMPETENCIES IN THE MANAGEMENT TRAINING OF HEALTH - O. Zadvornaya; V. Alekseev; K. Borisov; N. Kasatkina; I. Shurandina (Модернизация, инновация, развитие, 2016)
The article considers modern problems of management training of health described the long experience of the Department of international health, Russian medical Academy of postgraduate education in the field of additional professional education of managers of medical organizations using methods of activating the learning process. The basis of realization of programs of management training was competencybased approach, involving the assessment and development of professional competencies of heads of health organizations on a modern methodological basis, aimed at improving the efficient use of labor and human resources of the organization.